2005
DOI: 10.1007/s10709-003-2717-1
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis and genotype-environment interaction for quantitative trait loci affecting flowering time in Arabidopsis thaliana

Abstract: A major goal of evolutionary biology is to understand the genetic architecture of the complex quantitative traits that may lead to adaptations in natural populations. Of particular relevance is the evaluation of the frequency and magnitude of epistasis (gene-gene and gene-environment interaction) as it plays a controversial role in models of adaptation within and among populations. Here, we explore the genetic basis of flowering time in Arabidopsis thaliana using a series of quantitative trait loci (QTL) mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 56 publications
(36 reference statements)
5
84
0
Order By: Relevance
“…Flowering time is highly variable between accessions of Arabidopsis (22). Variation in flowering time also exists between Ler and Cvi, and several studies have reported QTLs for this trait (26)(27)(28). Although flowering starts much later, the expression of genes that indicate commitment to flowering are already apparent at a very early stage and find their transcription peak in the seedling stage (29,30).…”
Section: A Dual Approach For the Construction Of Regulatory Networkmentioning
confidence: 99%
“…Flowering time is highly variable between accessions of Arabidopsis (22). Variation in flowering time also exists between Ler and Cvi, and several studies have reported QTLs for this trait (26)(27)(28). Although flowering starts much later, the expression of genes that indicate commitment to flowering are already apparent at a very early stage and find their transcription peak in the seedling stage (29,30).…”
Section: A Dual Approach For the Construction Of Regulatory Networkmentioning
confidence: 99%
“…QTL 9 environment interactions Ungerer et al (2003) described the ability of a genotype to modify phenotypic expression in response to different environmental conditions as phenotypic plasticity, which arises in nature from interactions between QTL and environments at the molecular level (Yang et al 2007a). Several examples of QEIs for agronomic traits such as plant height, heading date (Zhang et al 2008(Zhang et al , 2009Yang et al 2007b;Campbell et al 2003) showed that the influence of particular chromosomal regions differed across environments.…”
Section: Genetic Dissections and Pleiotropy Of Qtlsmentioning
confidence: 99%
“…The timing of inflorescence developmental events and overall architecture can be influenced to a great extent by environmental cues such as nutrient availability, drought stress, light quality, photoperiod and vernalization (Ungerer et al 2003;Van-Dijk and Hautekèete 2007). From the genetics viewpoint, the number of loci involved in regulating flowering time has been shown to depend upon both the ecotype and the environment in which the plants are grown (Clarke et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…From the genetics viewpoint, the number of loci involved in regulating flowering time has been shown to depend upon both the ecotype and the environment in which the plants are grown (Clarke et al 1995). Indeed, genetic and environmental factors are inextricably linked and phenotypic expression is determined by their joint effects (Ungerer et al 2003). Moreover, in the case of eucalyptus species, early flowering has shown to be a highly heritable trait (Chambers et al 1997).…”
Section: Introductionmentioning
confidence: 99%